Feed production for sustainable aquaculture: A Bibliometric Network Analysis - Geremia, Eugenio; Grande, Umberto; Muscari Tomajoli, Maria Teresa; Petito, Adriana; Fasciolo, Gianluca; Napolitano, Gaetana (Ecological Questions, 2024)
In recent years, aquaculture has played a fundamental role in human nutrition and livestock for the ability to produce different animal and vegetable protein and lipid sources essential for human and animal health. However, the growing increase in aquaculture has led to a greater demand for ingredients composing feed for aquatic organisms, many of which are derived from wild fish making the aquatic feed production an unsustainable process. For this reason, the aquaculture sector has expanded experimentation to search for alternative ingredients to reduce environmental impact. This study explored the global scientific literature on sustainable aquaculture with particular reference to feeding using VOSviewer software, which allows for generating, visualizing, and exploring maps based on bibliometric network data. The results allowed a comprehensive overview of the scientific literature on sustainable aquaculture through network maps displaying the relationships among keywords, authors, countries, and journals. In detail, this paper highlighted that in the last years, particularly in recent decades, the research widely focused attention on different aspects of the sustainable aquaculture field. The first journal that researched sustainable aquaculture was the Aquaculture Journal, and the leading countries that pursued this type of research were the USA, UK, and China. Concerning the co-occurrence, the top keywords were aquaculture, sustainability, animals, nonhuman, and sustainable development, highlighting a growing interest in research on microalgae, diet, fishmeal, and climate change. The description of the current state of the art in sustainable aquaculture reported in this article highlighted that the combined use of social network analysis and bibliometrics allows exploring the development of research in specific fields of science and lays the foundations for delving into questions that have not yet been sufficiently investigated.